2019
DOI: 10.1007/s11930-019-00192-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Body Weight on Sexual Function in Men and Women

Abstract: Purpose of review: Obesity is a growing problem worldwide. This review aims to summarize the literature on the effects of weight on sexual function in both men and women from the past 5 years. Recent findings: In recent population-based studies of men and women, no relationship between weight and sexual function was identified. However, in studies of special populations such as women with gestational diabetes, polycystic ovarian syndrome (PCOS), pelvic organ prolapse or urinary incontinence, weight affected so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Sexual health is a state of physical, mental and social well‐being related to sexuality; various pathologies affect sexual health and can result in sexual dysfunction (Chou, Cottler, Khosla, Reed, & Say, 2015). MO influences all the dimensions of sexual functioning (Bates, Pastuszak, & Khera, 2019), and therefore, men with MO are prone to male sexual dysfunction (MSD) (Carr, Murphy, Batsoin, & Springer, 2014; Sarwer et al., 2015). MSD is an underestimated problem in MO (Arolfo, Scozzari, Di Benedetto, Vergine, & Morino, 2020), and 50% of men mention sexual dissatisfaction (Pomares‐Callejón, Ferrer‐Márquez, & Solvas‐Salmerón, 2018; Steffen et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sexual health is a state of physical, mental and social well‐being related to sexuality; various pathologies affect sexual health and can result in sexual dysfunction (Chou, Cottler, Khosla, Reed, & Say, 2015). MO influences all the dimensions of sexual functioning (Bates, Pastuszak, & Khera, 2019), and therefore, men with MO are prone to male sexual dysfunction (MSD) (Carr, Murphy, Batsoin, & Springer, 2014; Sarwer et al., 2015). MSD is an underestimated problem in MO (Arolfo, Scozzari, Di Benedetto, Vergine, & Morino, 2020), and 50% of men mention sexual dissatisfaction (Pomares‐Callejón, Ferrer‐Márquez, & Solvas‐Salmerón, 2018; Steffen et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Individual, social and environmental factors also contribute to MSD, stigma and loss of quality of life in MO patients (Nath, 2019; Sharman et al., 2016). Although MO treatment has focused on diet, physical exercise and drugs (Baillot, Mampuya, Comeau, Méziat‐Burdin, & Langlois, 2013; Srivastava & Apovian, 2018), bariatric surgery has been shown to be a reliable method of loss of weight improving quality of life (Kabu & Özbayır, 2019; Wingfield et al., 2016), body image and sexual functioning (Bates et al., 2019; Quinn‐Nilas, Benson, Milhausen, Buchholz, & Goncalves, 2016). Men with MO, driven by loss of mobility, confidence and self‐esteem, try to be included in a bariatric surgery programme (Wu & Berry, 2018), whose inclusion criteria are as follows: being an adult with a BMI ≥40 kg/m 2 ; or being an adult with a BMI of 35–39.9 kg/m 2 and having associated chronic conditions (type 2 diabetes, hypertension, hyperlipidemia) (Landecho, Valentí, Moncada, & Frühbeck, 2017; Sabench et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…To date, the effect of obesity on sexual life in women remains inconclusive. Some studies found no association between BMI and FSF [ 44 , 45 ]; while others showed increased FSD in overweight and obese women [ 46 48 ]. Herein, we observed obese women had improved FSF.…”
Section: Discussionmentioning
confidence: 99%
“…In general, 56% of the 25 women enrolled in this study were at risk for sexual dysfunction symptoms (FSFI score 26). Some studies involving special populations such as women with GDM, pelvic organ prolapse, polycystic ovarian syndrome, and urinary incontinence have implied that weight gain negatively im-pacts some aspects of sexual function [32]. However, Pilates exercises did not improve sexual function in women with GDM.…”
Section: Human Movementmentioning
confidence: 98%